International capital flows in the 1990s : the role of institutional investors. - D'ARISTA, Jane W. (1996)
Discusses ways in which shifts in channels for international capital flows in the 1990s affected the implementation of macroeconomic policy in developing countries. Describes some of the strategies used to counter the undesirable effects of large inflows of foreign portfolio investment.